Effect of corrosion degradation on failure mechanisms of aluminium/steel clinched joints. (15th December 2015) - Calabrese, L.; Proverbio, E.; Galtieri, G.; Borsellino, C.
Abstract: The effect of corrosion phenomena in critical environmental conditions on the mechanical performance of steel/aluminium hybrid joints, obtained by clinching technique, was studied by ageing in salt spray environment. The investigation was carried out on asymmetrical joints with total thickness of 2.5 mm. The joint strength at varying ageing time was determined by means of single lap shear tests. The experimental results have shown that corrosion degradation phenomena significantly affect the performance and failure mechanisms of the joints, causing premature failure of the joint at very low stress level. Moreover, it was observed that the joint geometry characterized by thicker aluminium foil, had good durability properties showing acceptable mechanical properties even at long ageing times. The fracture modes have been analysed in all the above-mentioned conditions and a failure map, at increasing ageing time, for the two joint geometries has been proposed. Graphical abstract: Highlights: Clinched aluminium–carbon steel joints degrade due to ageing in salt spray fog test. Mechanical performances of the joints decrease significantly at increasing ageing time. Corrosion degradation of sheets is related to metal joint configuration. A simplified theoretical model was proposed efficiently to interpret the corrosion effect.